Fostering Environmental Awareness Through Eco-Literacy in Novels: A Bibliometric Review - Khasanah, Venus; Anoegrajekti, Novi; Setiadi, Samsi; Abdullah, Khairul Hafezad (Fronteira: Journal of Social, Technological and Environmental Science, 2024)
Due to rising worldwide environmental issues, eco-literacy and environmental consciousness have received emphasis in recent years. This phenomenon implicitly suggests that novels can significantly elucidate intricate ecological concepts. This study aims to uncover the underlying currents that shape the discourse around eco-literacy in novels and their influence on societal perceptions of the environment. This study used Scopus and Web of Science (WoS) databases to gather and analyse datasets. ScientoPy and VOSviewer were then used to analyse the retrieved datasets. This study found that temporal trend analysis showed a gradual increase in research production, notably after 2005, showing a growing interest in the connection between eco-literacy and novel studies. The prevalence of keywords such as “environmental education”, “eco-criticism”, and “environmental communication” demonstrates the significance of literature as a tool for cultivating environmental awareness, critical analysis, and effective communication in novels. This study contributes to the field by comprehensively evaluating the temporal patterns, thematic themes, and collaborative networks within eco-literacy domains and new research